The Transformation of the Financial Autonomy of Local Governments - András Bencsik (Institutiones Administrationis)
Ensuring a broad degree of financial autonomy is a fundamental issue for local government. In the context of the administrative modernization of recent years, several legislative measures have been taken which have directly or indirectly limited the financial and economic autonomy of local governments in Hungary. The paper gives a brief overview of the development of the Hungarian local government system in 1990, comparing the initial regulation with the standards of the European Charter of Local Self-Government. It discusses, then, the restructuring of the system in 2011, and lists the legal institutions which, in the author’s view, have led to restrictions on local government management. The paper covers the introduction of the task-financing system, the establishment of district offices, the restructuring of the role of county governments, and the constitutional and other legal obstacles to municipal borrowing.